Citation to Target Journal; A Motivation Based on Normative Citing Conformity - Saeideh Ebrahimy; Farideh Osareh (International Journal of Information Science and Management, 2015)
Research on citation behaviors shows that authors tend to cite the articles of the journals to which they have sent their own articles to be published (Target Journal). Experts in this field have clarified this phenomenon in different ways. The present study follows different explanatory presentations with regard to Citing Conformity Factor. The research has been done in two parts: 1. Survey Method, and 2. Citation analysis method. The results of regression analysis suggest that some part of this phenomenon’s variance is justified based on Normative Citing Conformity. In line with conformity with group norms and through having the motivation for receiving rewards, the authors cite the articles in target journal. The relationship between Citing Conformity Factors (Normative, Informational, and Identification) and the motivation to cite target journal has been analyzed in this research for the first time.